Perbedaan Sensitifitas Air Rebusan Daun Sirih Hijau dengan Daun Sirih Merah dalam Menghambat Pertumbuhan Bakteri Escherichia coli Menggunakan Metode Difusi - Kamarudin Kamarudin; Suwandi Edy (Indonesian Journal of Herbal and Biomedical Research, 2026)
Green betel leaves contain essential oils, tannins, alkaloids, flavonoids, phenols, and steroids. Conversely, red betel leaves contain chemical compounds such as flavonoids, alkaloids, tannins, and essential oils. The compounds present in red betel leaves are secondary metabolites that can be utilized as medicinal agents. This study aimed to evaluate the differences in the antibacterial efficacy of green and red betel leaf decoctions in inhibiting the growth of Escherichia coli using the diffusion method. A comparative research design was employed to determine the magnitude of the differences between the observed groups. The results demonstrated that across 16 samples of green betel leaf decoction, the zone of inhibition ranged from 9 mm to 11 mm, with a mean of 10 mm. In contrast, the 16 samples of red betel leaf decoction exhibited a minimum inhibition zone of 11 mm and a maximum of 13 mm, with a mean inhibition zone of 11.88 mm (~12 mm). The Mann-Whitney U test yielded a p-value of 0.000 (p < 0.05), indicating a statistically significant difference in inhibitory activity between green and red betel leaf decoctions against the growth of Escherichia coli.